Cladopelma Kieffer from the Sino-Indian Region (Diptera: Chironomidae) - Yan, Chuncai; Jin, Zhaohui; Wang, Xinhua (Zootaxa, 2008)
The Sino-Indian species of the genus Cladopelma Kieffer are reviewed and one new species from China, C. costum sp. n., is described and illustrated as male. The males of C. edwardsi (Kruseman) and C. virescens (Meigen) from China are re-examined. Type material of Cryptotendipes inawaabeus Sasa, Kitami et Suzuki, Harnischia daitoheia Sasa et Suzuki, H. ginzandeeus Sasa et Suzuki, H. inadeeus Sasa, Kitami et Suzuki, H. sibacedea Sasa, Sumita et Suzuki, H. simantocedea Sasa, Suzuki et Sakai from Japan and Cladopelma indicum Bhattacharyay, Duta et Chaudhuri from India are reexamined, and all regarded as new synonyms of C. edwardsi. Cladopelma onogawaprima Sasa is regarded as a new synonym of C. hibaraprima Sasa and the species is transferred to Cryptotendipes as a new combination. Cladopelma kamalanagari Maheshwari et Agarwal from India is transferred to Paracladopelma as a new combination. A key to all known males of Cladopelma is provided.